Association of immunoglobulin G4‐related disease with a family history of malignancy: A retrospective study of 168 cases. Issue 2 (14th December 2021) - Hu, Diping; Li, Yanhong; Zhou, Yu; Luo, Yubin; Cheng, Lu; Tan, Chunyu; Zhang, Qiuping; Zhao, Yi; Liu, Yi
Abstract: Objective: Immunoglobulin G4‐related disease (IgG4‐RD) is a systemic immune‐mediated fibroinflammatory condition. Previous studies have indicated relationships between malignancy and autoimmunity. This retrospective cohort study aimed to determine IgG4‐RD incidence and clinical features in patients with a family history of malignancy. Methods: To analyze the relationship between IgG4‐RD and family history of malignancy, we reviewed IgG4‐RD patients with a family history of malignancy diagnosed in various departments in West China Hospital, Sichuan University from December 2012 to September 2019. Clinical data and laboratory features were compared between IgG4‐RD patients with and without a family history of malignancy. Results: Among 168 enrolled patients with IgG4‐RD, 22 (13.1%) had a family history of malignancy. The most frequently involved system in family members with malignancy was the digestive system (38.5%). Among patients with a family history of malignancy, the most frequently involved organs in IgG4‐RD were the pancreas (31.9%) and lymph nodes (31.9%). Age at symptom onset was older in IgG4‐RD patients with a family history of malignancy than in patients without a family history of malignancy (50–59 years: 36.3% vs. 16.4%, p  = 0.0393). Hemoglobin ( p  = 0.0172) and albumin ( p  = 0.0247) levels were higher and globulin ( p  = 0.0232) levels were lower in patients with a family history of malignancy. Conclusions: Our findings suggest that a family history of malignancy may be associated with IgG4‐RD development. We hypothesize that genetic susceptibility may be involved in the pathogenesis of IgG4‐RD. Key points: Immunoglobulin G4‐related disease (IgG4‐RD) is a systemic immune‐mediated fibroinflammatory condition. Previous studies have indicated relationships between malignancy and autoimmunity. This retrospective cohort study found that a family history of malignancy was present in 13.1% of IgG4‐RD patients. Family history of malignancy may be associated with IgG4‐RD development and genetic susceptibility may be involved in the pathogenesis of IgG4‐RD, but further studies are needed to test this hypothesis and explore possible susceptibility genes. Abstract : IgG4‐RD and family history of malignancy.